The impact of the SARS-CoV-2 infection on the risk of developing preeclampsia - Anna Kozłowska; Anna Korzeniowska; Karolina Gendek; Ilona Gąbka; Weronika Dalmata; Jan Dąbrowski; Ewelina Zygmunt-Siembida; Dariusz Chojęta (Kazimierz Wielki University, 2023)
Introduction and purpose:    The COVID-19 pandemic has significantly affected the health, life and quality of life of many people around the world. It caused huge changes in the daily functioning of entire societies. Pregnant women are a unique group of people who are particularly at risk. They are accompanied by fear for their health, but also fear of the impact of the disease on their offspring. The pandemic has also caused new challenges for mothers-to-be that have not occurred so far. In this paper, we would like to present the current state of knowledge on the impact of SARS-CoV-2 infection on the risk of developing pre-eclampsia.   State of knowledge:   We analyzed studies showing the impact of COVID-19 infection on the health of pregnant women, especially on the risk of developing pre-eclampsia. Data from many studies are contradictory. Some studies do not indicate a significant impact of coronavirus infection on the development of pre-eclampsia. Some of them confirm a higher incidence of pre-eclampsia in pregnant women with confirmed COVID-19 infection.   Conclusions:   Despite the experience gained, there are still many unknowns. Thanks to research, we have more and more knowledge about the course of COVID-19 in pregnant women and its impact on their lives. Many observations are still needed to formulate clear conclusions about the impact of COVID-19 on the risk of developing pre-eclampsia. It is also necessary to continue to educate women, encourage compliance with the recommendations of doctors and the World Health Organization to prevent the spread of coronavirus.